2019
DOI: 10.3389/fphar.2019.00159
|View full text |Cite
|
Sign up to set email alerts
|

Epoxyeicosatrienoic Acid-Based Therapy Attenuates the Progression of Postischemic Heart Failure in Normotensive Sprague-Dawley but Not in Hypertensive Ren-2 Transgenic Rats

Abstract: Epoxyeicosatrienoic acids (EETs) and their analogs have been identified as potent antihypertensive compounds with cardio- and renoprotective actions. Here, we examined the effect of EET-A, an orally active EET analog, and c -AUCB, an inhibitor of the EETs degrading enzyme soluble epoxide hydrolase, on the progression of post-myocardial infarction (MI) heart failure (HF) in normotensive Hannover Sprague-Dawley (HanSD) and in heterozygous Ren-2 transgenic rats (TGR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Furthermore, we have examined the association of R287Q variant with the enzyme activity of soluble epoxide hydrolase and found a significant lower level of the 11,12-DHET in the mutation group than in the wild-type group. Our findings are biologically plausible, as soluble epoxide hydrolase is an enzyme responsible for rapid conversion of cytochrome P450 arachidonic acid epoxygenase metabolites, to inactive or less active DHETs [23,24]. For practical reasons, our findings represent a novel approach to understanding molecular mechanisms involved in the pathogenesis of hypertension and may help target therapies according to the genotypes of R287Q variant for patients with primary hypertension to optimize prevention strategies.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, we have examined the association of R287Q variant with the enzyme activity of soluble epoxide hydrolase and found a significant lower level of the 11,12-DHET in the mutation group than in the wild-type group. Our findings are biologically plausible, as soluble epoxide hydrolase is an enzyme responsible for rapid conversion of cytochrome P450 arachidonic acid epoxygenase metabolites, to inactive or less active DHETs [23,24]. For practical reasons, our findings represent a novel approach to understanding molecular mechanisms involved in the pathogenesis of hypertension and may help target therapies according to the genotypes of R287Q variant for patients with primary hypertension to optimize prevention strategies.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, the improved post-MI LV function is more likely attributable to EET-B beneficial actions during CHF progression as it was previously demonstrated for other EET-based pharmacological interventions [ 8 , 10 , 11 , 18 , 37 , 48 ]. Finally, in a recent work we demonstrated that sEH inhibitor c-AUCB and EET analog EET-A, given alone or in combination at reperfusion attenuated the progression of post-MI LV systolic dysfunction only in Sprague-Dawley but not in hypertensive Ren-2 transgenic rats in spite of blood pressure reduction [ 19 , 49 ]. Moreover, these findings support previous findings indicating that the protective action of EET analogs against various cardiovascular diseases is independent of their antihypertensive actions.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, experimental studies have demonstrated EETs mediate a myriad of cellular and metabolic pathways, which are cardioprotective toward several pathologies including HF [ 187 , 188 , 189 , 190 ]. For instance, Cao et al reported that using ( S )-2-(11-(nonyloxy) undec-8( Z )-enamido) succinic acid (NUDSA), an EET agonist, in a murine model of myocardial infarction (MI) is associated with improved systolic dysfunction, decreased myocardial fibrosis and limited remodeling in post-infarcted HF [ 191 ].…”
Section: N-3 and N-6 Polyunsaturated Fatty Acids (Pufas)mentioning
confidence: 99%
“…Novel pharmacological approaches that selectively inhibit sEH have evolved as clinical tools in various cardiovascular diseases, including hypertension, cerebral ischemia, cardiac ischemia, cardiac hypertrophy, myocardial infarction and atherosclerosis [ 202 , 203 , 204 , 205 , 206 , 207 ]. Pharmacological sEH inhibition is demonstrated to improve both LV diastolic and systolic function and attenuate myocardial remodeling in established HF [ 188 , 208 , 209 ]. Treatment with cis -4-[4-(3-adamantan-1-yl-ureido) cyclohexyloxy] benzoic acid (c-AUCB)-attenuated increased systolic and diastolic LV cavity diameter following ischemia/reperfusion injury in rats.…”
Section: N-3 and N-6 Polyunsaturated Fatty Acids (Pufas)mentioning
confidence: 99%
See 1 more Smart Citation